Improvement in itch and other psoriasis symptoms with brodalumab in phase 3 randomized controlled trials. (30th March 2018) - Gottlieb, A.B.; Gordon, K.; Hsu, S.; Elewski, B.; Eichenfield, L.F.; Kircik, L.; Rastogi, S.; Pillai, R.; Israel, R.
Abstract: Background: Patients with psoriasis have lesional symptoms, including itch, which can reduce quality of life. The efficacy and safety of brodalumab, an interleukin‐17 receptor A antagonist, in treating moderate‐to‐severe psoriasis have been reported in three randomized, controlled, phase 3 trials (AMAGINE‐1/‐2/‐3). Objective: The effect of brodalumab on lesional symptoms was assessed using the psoriasis symptom inventory (PSI), a validated patient‐reported instrument. Methods: Patients were randomized to receive brodalumab (140 or 210 mg every 2 weeks [Q2W]), placebo (AMAGINE‐1/‐2/‐3), or ustekinumab (AMAGINE‐2/‐3) during a 12‐week induction phase, followed by a maintenance phase through week 52. Patients electronically rated the severity of PSI items (itch, burning, stinging, pain, redness, scaling, cracking and flaking) during the previous 24 h on a scale of 0 (not at all severe) to 4 (very severe). At each visit, the PSI total score responder status was assessed, with responders defined as having an average weekly total inventory score ≤8 with no item score >1 at week 12. Results: Across AMAGINE‐1/‐2/‐3, brodalumab was associated with improvements in PSI total scores and itch scores vs. placebo from week 2 through week 12 ( P  < 0.001 in both domains). In AMAGINE‐2/‐3, brodalumab 210 mg Q2W demonstrated faster onset of PSI total score and itch responses (week 2, 22.1% and 36.4%, respectively) vs. ustekinumab (week 2, 6.9% and 17.1%, respectively) and was associated with improved itch responses vs. ustekinumab after 52 weeks of constant treatment. Conclusion: Brodalumab demonstrated rapid, robust improvements in symptoms assessed by the PSI, including itch, vs. placebo and ustekinumab.